Pengaruh Dana Pihak Ketiga, Bopo, Car , Dan Npl Terhadap Kinerja Keuangan (Studi Kasus pada sub sektor Perbankan Umum yang terdaftar di Bursa Efek Indonesia periode 2016-2018) - Nurfarida Nurfarida; Ronny Malavia Mardani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract            The research is to analyzed the impact of third party fund (DPK), Operational cost on Operational income (BOPO), Capital Adequacy Ratio (CAR) and Net Performing Loan (NPL) to financial performance (ROA). This type of research is explanatory. The data used in the form of secondary data. The population and sample are all banking companies listed on the Indonesia Stock Exchange in 2016-2018.The sampling technique is to use purposive sampling techniques and data testing techniques used in this study normality test, classic assumption test, multiple linear regression analysis and hypothesis testing.            Based on the result of this research known that partial, third party fund (DPK) have negative and insignificant impact on financial performance (ROA) with a sig. 0,007  < 0,050. Operational cost on operational income (BOPO) have negative impact and insignificant to financial performance (ROA) with sig. 0,000 <0,050, capital adequacy ratio (CAR) have positive and significant impact to financial performance (ROA) with sig. 0,072 >  0,050 and Net Performing Loan (NPL) a positive and significant impact on financial performance with sig. 0,843 < 0,050. While simultaneously or together, third party fund (DPK) , Operational cost on operational income (BOPO), Capital adequacy ratio (CAR) and Net performing Loan (NPL) have impact to financial performance (ROA) with sig. 0,000 <0,050.  Key words : Third Party Fund (DPK), and Operational cost to operational income (BOPO),  Capital Adequacy Ratio (CAR) and Net Performing Loan (NPL), Financial performance  (ROA).